2010
DOI: 10.1016/j.mrfmmm.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary examination of polymorphisms of GSTM1, GSTT1, and GSTZ1 in relation to semen quality

Abstract: Background Environmental, lifestyle, and occupational exposures on semen quality have been investigated in epidemiological studies with inconsistent results. Genetic factors involved in toxicant activation and detoxification have been examined in relation to the risk of outcomes such as cancer, cardiovascular, and neurologic disorders. However, the effect of common genetic variants in the metabolism of toxicants on semen quality parameters has rarely been evaluated. In this analysis, we evaluated functional SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…This finding had been previously confirmed in fertile men with good semen quality [17]. Olshan et al showed that gene polymorphisms of GSTM1, GSTT1, and GSTZ1 are not correlated with sperm quality.…”
Section: Discussionmentioning
confidence: 56%
“…This finding had been previously confirmed in fertile men with good semen quality [17]. Olshan et al showed that gene polymorphisms of GSTM1, GSTT1, and GSTZ1 are not correlated with sperm quality.…”
Section: Discussionmentioning
confidence: 56%
“…Most findings confirmed its influence on sperm concentrations (Aydemir et al, 2007;Finotti et al, 2009;Olshan et al, 2010) but also on sperm motility and increased oxidative damage of sperm plasma membrane in idiopathic infertility patients with GSTM1 null genotype (Aydemir et al, 2007). GSTM1 null genotype has also been studied in relation to susceptibility to male infertility, particularly to idiopathic oligozoospermia (Wu et al, 2013) and oligoasthenoteratoa zoospermia (OAT) (Tang et al, 2012).…”
Section: Discussionmentioning
confidence: 70%
“…GST genes have been studied in relation to semen quality (Olshan et al, 2010) and genetic susceptibility of infertility with impaired spermatogenesis in men (Xu et al, 2013;Ying et al, 2013). Polymorphisms in GSTs genes, mostly null and non-null genotype, were associated with oligoazoospermia, azoospermia and idiopathic male infertility risk (Aydemir et al, 2007;Wu et al, 2008;Finotti et al, 2009;Roshdy et al, 2014) or DNA damage of sperm exposed to air pollution (Rubes et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that not all the GST isoforms may play a significant role in the protection of spermatozoa against oxidative stress; for example, the levels of GST A1-1 and P1-1 in seminal plasma are similar in fertile or infertile men [87]. Recently, it was reported that GSTM1, GSTT1, and GSTZ1 polymorphisms seem not to be associated with sperm quality in humans, but only GSTT1 was associated with reduced sperm concentration [88]. Based on all these studies, it is evident that GSTs are playing different roles depending on the isoform considered and more research is necessary to have a complete picture of the participation of this large family of antioxidant enzymes in male reproduction.…”
Section: Glutathione Transferasesmentioning
confidence: 99%